Pengaruh Desain Stasiun Kerja Dengan Pendekatan Participatory Ergonomics untuk Meningkatkan Produktivitas Karyawan: Studi Kasus SMK Az-Zawiyah Tanjung Batu - R.A. Amareta Rezka; Christofora Desi Kusmindari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the context of education, the success of an institution is not only determined by the quality of curriculum and teaching, but also by adequate working environment conditions. Therefore, this study aims to investigate the effect of workstation design with a participatory ergonomics approach on employee productivity in the teachers' room and principal's room. The result of this study is that there is an influence of workstation design elements, layout and physical environment on the application of Participatory Ergonomics in improving employee productivity of SMK Az-Zawiyah Tanjung Batu. This is because the sig t value of the workstation design variable is 0,007 < α = 0,05, the layout variable is 0,012 < α = 0,05, and the physical environment variable is 0,009 < α = 0,05. There is a joint influence (simultaneously) elements of workstation design, layout, and physical environment on employee productivity SMK Az-Zawiyah Tanjung Batu this is because the sig value F variable workstation design, layout, and physical environment amounted to < 0,001 < α = 0,05.